Anatomical study and clinical significance of rami communicantes of the lumbar spine. Issue 4 (31st January 2022) - Zheng, Zhiyang; Ma, Runxun; Zhang, Rusen; Liu, Zezheng; Liu, Zexian; Chen, Junjie; Xu, Yejie; Zhou, Xinying; Zhao, Qinghao; Li, Qingchu
Abstract : Background and objectives: Rami communicantes (RC) infiltration and radiofrequency lesions are new techniques for the treatment of discogenic low back pain (DLBP). Their efficacy is controversial, and the classification of RC remains unclear. We aimed to explore the differences between RC and reclassify RC according to their anatomical characteristics. Methods: Sixteen sides of the lumbar spine from eight adult male embalmed cadavers were dissected. The presence of RC was noted. The morphology, origin, distribution, course, quantity and spatial orientation of RC on the lumbar spine were examined. The length and width of the RC were measured by a caliper. Results: A total of 213 RC were found in the 8 cadavers in the lumbar region. RC were divided into three types: superficial rami (70, 32.86%), which penetrated the psoas major (PM) and ran above the aponeurosis of the PM; deep rami (125, 58.69%), which ran along the waist of the vertebral body beneath the aponeurosis of the PM; and discal rami, which ran over and adhered to the surface of the intervertebral disc. Superficial rami were divided into two subtypes: oblique rami (45, 21.13%) and parabolic rami (25, 11.74%), which crossed the vertebra and the disc in an oblique and a parabolic course, respectively. Conclusions: RC should play an important role in the innervation of the lumbar spine. Detailed knowledge of RC in the lumbar region may help surgeons improve the efficacy of infiltration and percutaneous radiofrequency as a supplementary treatment for DLBP.